Effects of moringa oleifera supplementation combined with resistance exercise on immune responses and bone turnover markers among young men - Muin, Maziana Abdul (2018)
INTRODUCTION: Proper immune function and healthy bone is required for maintaining daily routine of an individual. To date, no study has been carried out to investigate possible benefits of Moringa oleifera supplementation combined with resistance exercise on immune responses and bone turnover markers among young men. PURPOSE: Therefore, the present study was carried out to determine the effects of Moringa oleifera supplementation combined with resistance exercise (MOEx) compared to Moringa oleifera supplementation alone (MO), resistance exercise alone (Ex) and control (C) groups on immune responses and bone turnover markers among young men. METHODS: Forty sedentary young men (age: 22.1 ± 1.3 years old) were recruited and were randomised into four separate groups: placebo without exercise control (C), resistance exercise alone (Ex), Moringa oleifera supplementation alone (MO) and resistance exercise with Moringa oleifera supplementation (MOEx). Participants in the Ex and MOEx groups performed resistance exercise 3 times per week for 6 weeks which consisted of 10 different exercises. Participants were required to perform 3 sets of 10-15 repetitions of resistance exercise per set. Participants in the MO and MOEx groups consumed Moringa oleifera (300 mg of 100% Moringa oleifera leaf powder each capsule) and participants in the C and Ex groups consumed placebo twice daily for 6 weeks. Participants’ body height, weight, blood pressure andresting heart rate were measured at pre- and post-tests. Blood samples were collected at pre- and post-tests after an overnight fast. Blood samples were used to analyse total WBC, lymphocytes, monocyte, T lymphocyte (CD3+, CD4+ and CD8+) and B lymphocyte (CD19+) counts. Blood samples were also used to analyse concentrations of alkaline phosphatase (ALP), osteocalcin (OC) and cross-linked C-terminal telopeptide of collagen alpha-1 (1CTP). A mixed analysis of variance (ANOVA) was performed to determine the significance of the differences between and within groups. RESULTS: It was found that combination of resistance exercise and Moringa oleifera did not significantly (p > 0.05) induce better effects on immune responses and bone turnover markers concentration compared to control, resistance exercise alone, and MO supplementation alone. CONCLUSION: Six weeks of combined MO supplementation and resistance exercise did not significantly enhance immune responses and bone turnover markers among sedentary young men.